Formal and Informal Language Styles Used in It’s Me Marsya Movie - Ida Ayu Putri Gita Ardiantari; Ni Wayan Supartini Ningsih (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The purpose of this study is to analysis the style of language used by all the characters in the film "It's Me Marsya". In the film there are dialogues played by all the characters, there are many styles of language, but here the research focuses only on formal and informal language styles. This study obtains the factors of differences in formal and informal language styles. Language style can be found in the choice of words and grammar used in real-world communication or when watching movies. It is very important for people to express their ideas, the people who use that language style depend on who they are talking to and in which position they are speaking. This film is based on a true story that a little girl experiences about her magical friend, who becomes her playmate. His friend has accompanied him since he was two years old in the form of a Dutch child spirit. This type of research is qualitative research. The data collection method used in this study is the method of watching movies repeatedly, making transcription dialogs between characters, comparing scripts and transcripts to confirm the data, classifying data into various types of language styles used by the characters. Research data taken from conversational dialogue, which is transcribed in a movie. Then the research classifies based on the dominant type of language style. After analysis the data, the writer found that there are formal (40%) and informal (60%) language styles. It can be concluded that the dominant style of language is informal.